From InSAR‐Derived Subsidence to Relative Sea‐Level Rise—A Call for Rigor - P. S. J. Minderhoud; M. Shirzaei; P. Teatini (Earth's Future)
Abstract Coastal subsidence, the gradual sinking of coastal land, considerably exacerbates the impacts of climate change‐driven sea‐level rise (SLR). While global sea levels rise, land subsidence often increases relative SLR locally. Thiéblemont et al. (2024, https://doi.org/10.1029/2024ef004523) reached a remarkable milestone by providing a continental‐scale estimate of vertical land motion (VLM) across European coastal zones by utilizing European Ground Motion Service (EGMS) data, obtained from Interferometric Synthetic Aperture Radar (InSAR) data from Sentinel‐1 satellites. Their findings reveal widespread coastal subsidence, with nearly half of the coastal floodplains, including major cities and ports, subsiding at rates exceeding 1 mm/yr, thereby exacerbating relative SLR. The study emphasizes the critical role of InSAR‐data calibration, indicating that the EGMS geodetic reference frame significantly influences VLM estimates. This study highlights the need for a robust InSAR‐data processing framework to accurately interpret VLM and its relationship to relative SLR. The processing pipeline should ensure internal consistency of SAR data and rigorously assess output accuracy, considering also post‐processing effects. Correct interpretation of results is essential as InSAR satellites measure reflector movement, which may not always align with land surface movement, particularly in urban areas. Ignoring these discrepancies can lead to underestimation of subsidence rates. While InSAR data offers valuable research opportunities, it poses risks of oversimplification and misinterpretation, especially when linked to sea‐level change. We call for standardized processing workflows and cross‐disciplinary collaboration, essential for accurate VLM interpretations, particularly in coastal cities and river deltas, to ultimately enhance the reliability of relative SLR projections and inform effective coastal management strategies.